The impact of internal company dynamics on sustainable circular business development: Insights from circular startups - Charleen von Kolpinski; Devrim Murat Yazan; Luca Fraccascia (Business Strategy and the Environment, 2022)
The circular economy is commonly acknowledged as a solution to ecological problems such as resource depletion and waste emissions. New economic opportunities emerge by transitioning from a linear to a circular economy and innovative business models are needed to translate these opportunities into business reality. In recent years, researchers have investigated a variety of approaches to circular business models, but few studies have been conducted associating internal company dynamics with sustainable circular business approaches. Consequently, the purpose of this study is to investigate the internal dynamics of young and small-scale companies in Germany that adopt a sustainable circular business model. This study focuses on internal barriers, enablers, competences and drivers to sustainable circular business model implementation. A case-based research design was applied, drawing on semi-structured interviews with 12 founders of businesses and organisations with a sustainable circular business model. The study develops four strategies to overcome barriers to sustainable circular business model adoption in young and small-scale companies: (1) human-centeredness in all activities affected by circular business model adoption, (2) high commitment for circularity on the managerial level, (3) requirement of special skills and competences and (4) consideration of cultural aspects inside and outside the company. Further empirical research about established and international incumbents with a sustainable circular business model is needed to be able to compare the internal dynamics of big and small companies in international contexts.
Keywords: 650; circular business model; circular economy; circular startup; internal dynamics; small-medium enterprises; sustainability